Analisis RUU Anti Trafficking di Indonesia - Rahmah, Wahyuni Shifatur (Musawa Jurnal Studi Gender dan Islam, 2006)
Trafficking was initially associated with prostitution but, infact, it includes some other exploitations and slavery. Human trafficking keeps growing and its farm and complexity are changing from time to time_the only persistent thing is its characteristic of human exploitation. It is illegal activity and is against human rights: it is against the rights of its victims, which include women, children and worker. Trafficking is vulnerable to the emergence of violence against human beings, unwanted pregnancy, and sexually transmitted (STD) and infectious diseases. The networks of trafficking are currently well organized and, therefore, it demands a more serious and global attention to deal with the issue. Each country, including Indonesia, has to rethink about its system of law to be able to prosecute the traffickers and help the victims, both materially and immaterially. Some countries have ratified and implemented the anti-trafficking law. In Indonesia, however, the law is presently neither ratified nor implemented yet. The government of Indonesia, nonetheless, proclaimed the national action plan for the elimination of trafficking in women and children and made RUU (draft of laws) on anti, trafficking. So many women and children in Indonesia are waiting for the law that liberates them from any violence or exploitation and enables them to enjoy freedom of life. This draft, therefore, has to be immediately ratified.